Analysing health policy : a problem-oriented approach - Barraclough, Simon; Gardner, Heather (Marrickville, N.S.W. : Elsevier, 2008)
"Analysing health policy explores Australian health policy using a novel, problem-orientated approach. It shows the problem-solving techniques that are used when developing policy and demonstrates the skills of analysis and decision making.Introductory chapters explain the problem-orientated approach to health policy development and introduce the policy making process. Case studies then explore developments in health policy in both priority and topical areas. Chapters illustrate how policy-makers respond to perennial and emerging policy problems and demonstrate problem-solving approaches to the conception, development and implementation of health policy."--Provided by publisher.
Section 1. Health policy: an overview -- 1. A problem-oriented approach to health policy analysis -- 2. Health policy as a process -- 3. Institutional problems and health policy -- 4. Population health, the health system and policy -- 5. Health Impact Assessment in a policy context -- Section 2. Governance of the health system -- 6. Federalism and health -- 7. The public service and health -- 8. Municipal public health planning policy in Victoria -- 9. The health workforce: innovation, substitution and reform -- 10. Regulating complementary and alternative medicine practitioners -- Section 3. Values in health policy -- 11. Conflicting values in health information policy -- 12. The problem of trust in health policy -- 13. Dilemmas in end-of-life care: the Maria Korp case -- 14. The problem of failing to provide culturally and linguistically appropriate healthcare -- 15. Government, medical error, and problem definition -- Section 4. Responding to perennial or emerging health policy problems -- 16. The ageing population: in search of a policy -- 17. Reform of the pharmaceutical benefits scheme -- 18. Rethinking policy in mental health -- 19. Accommodating new technology: robotics in prostate cancer surgery -- 20. Implementing post-injury rehabilitation policy -- 21. Achieving uniformity in food hygiene regulation -- 22. Improving hygiene and children's health in remote Indigenous communities.
Includes bibliographical references and index.
Keywords: Medical policy -- Australia; Health planning -- Australia